THE EMERGENCE OF THE UZBEK PRESS IN TURKESTAN (UZBEKISTAN), THE STRUGGLE FOR SURVIVAL - Nilufar Namazova (Bright Mind Publishing, 2025)
This article discusses the establishment of the first national publications in Turkestan and the actions taken against them. It provides information about the measures of the Tsarist government, which occupied Turkestan, against the first national newspapers published in 1906 and the closure of these newspapers.
Keywords: Newspaper, Jadid, press, colony, Tsarist government, Okhrana.